Analysis Of Learning Productivity In Economic Mathematics Course Of Management Study Program S1 University Pamulang Academic Year 2021/2022 - Yanuarti, Maghfiroh; Asmarawati, Endah; Prasetyo, Hendri (International Journal of Educational Research & Social Sciences, 2022)
This study aims to analyze the productivity of blended learning in the economic mathematics course of the Management Study Program at Pamulang University. This study used qualitative descriptive methode. Techniques for collecting data using interview and documentation methods. The data in this study were obtained through interviews with 3 lecturers who are competent in economics mathematics courses and who already have lecturer certificates. The results showed that (1) Planning for blended learning is carried out by lecturers by preparing SAP, learning tools or materials, and learning media. (2) The implementation of blended learning is carried out online and through PTMT. (3) Evaluation of blended learning on the assessment of cognitive aspects is carried out through the LMS of Pamulang University in the Final Task 1 Meeting menu for online learning. (4) The learning process has been carried out in good and structured stages, starting from planning, implementation, and evaluation, so it can be said that learning with the blended learning model is running productively.